TINGKAT KETERBACAAN BUKU TEKS BAHASA INDONESIA KURIKULUM MERDEKA UNTUK KELAS X SMA/SMK - Hendrawanto, Yusuf (Jurnal Bahasa Indonesia Prima (BIP), 2023)
The ever-changing curriculum means that teaching materials, mainly textbooks, also continue to change. This change is not offset by the quality of textbooks discourse, which still not be appropriate to the students' readability level. This is shown in various studies that have been carried out, including by Yazidi et al. (2017), Saroni et al. (2017), Ginanjar (2020), and Susanti (2021), which resulted in the finding that the readability level of textbooks still does not match the students' readability level. This study aims to describe the readability of the Merdeka Curriculum Indonesian Language Textbook for Class X SMA/SMK entitled Intelligent Smart in Indonesian Language and Literature for Class X SMA/SMK. The method used in this study is a qualitative descriptive method-readability measurement formula using Fry Graph. The number of inner texts calculated using the Fry Graph is 23 texts. Based on the study result, 3 texts matched the legibility level of class X students, and 20 texts id not match the readability level of class X students. Twenty texts that did not match the readability level of class X students consisted of 1 text with a readability level that was too high/difficult, 17 texts with a readability level that was too low/easy, and 2 texts that did not match any readability level/invalid. Calculation of the readability level using the Fry Graph in the Indonesian Merdeka Curriculum Textbook for Class X SMA/SMK shows that the readability level of the Indonesian Merdeka Curriculum Textbook for Class X SMA/SMK entitled Smart Smart in Indonesian Language and Literature for Class X SMA/SMK is still not following the readability level of class X students.